2018
DOI: 10.1038/s41557-018-0092-x
|View full text |Cite|
|
Sign up to set email alerts
|

Dopant-induced electron localization drives CO2 reduction to C2 hydrocarbons

Abstract: The electrochemical reduction of CO to multi-carbon products has attracted much attention because it provides an avenue to the synthesis of value-added carbon-based fuels and feedstocks using renewable electricity. Unfortunately, the efficiency of CO conversion to C products remains below that necessary for its implementation at scale. Modifying the local electronic structure of copper with positive valence sites has been predicted to boost conversion to C products. Here, we use boron to tune the ratio of Cu t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
830
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 938 publications
(860 citation statements)
references
References 68 publications
18
830
3
9
Order By: Relevance
“…Of important note, the commercial viability of CO 2 RR to different products depends on a series of factors including not only the market demand of the product, but also the material, manufacturing, and separation costs. Although it is intuitively more desirable to control the selectivity toward higher‐valued products such as ethylene, ethanol, acetate, n ‐propanol, or even C 4 products, recent technoeconomic analysis unambiguously points out that the two‐electron electrochemical CO 2 RR to CO or formic acid is the most economically viable, whereas those C 2 –C 4 products other than propanol are not even profitable . This is understandable because the electricity cost is the major contributor to the operation cost of CO 2 electrolyzer.…”
Section: Fundamentals Of Electrochemical Co2 Reductionmentioning
confidence: 99%
“…Of important note, the commercial viability of CO 2 RR to different products depends on a series of factors including not only the market demand of the product, but also the material, manufacturing, and separation costs. Although it is intuitively more desirable to control the selectivity toward higher‐valued products such as ethylene, ethanol, acetate, n ‐propanol, or even C 4 products, recent technoeconomic analysis unambiguously points out that the two‐electron electrochemical CO 2 RR to CO or formic acid is the most economically viable, whereas those C 2 –C 4 products other than propanol are not even profitable . This is understandable because the electricity cost is the major contributor to the operation cost of CO 2 electrolyzer.…”
Section: Fundamentals Of Electrochemical Co2 Reductionmentioning
confidence: 99%
“…Electrochemical carbon dioxide reduction is ap romising solution for renewable energy storage,chemical/fuel production, and managing the global carbon balance. [1] To achieve the CO 2 reduction reaction (CO 2 RR) at al ow overpotential with high selectivity,good stability,and large current density, numerous material systems have been investigated, [2] including carbon materials, [3] metals, [4] metal oxides, [5] metal sulfides, [6] and so on. [7] However,t he mechanism of CO 2 activation and conversion, such as the catalytically active site and reaction pathway,r emains elusive.S ingle-atom catalysts (SACs) offer potential platforms for exploring the CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐known that the activity and selectivity of CO 2 RR catalysts strongly depend on the precise control of their structure, such as the content of defects, subsurface oxygen or Cu + species, the specific shape of the nanocrystals, or the surface composition and atomic ordering in bimetallic nanostructures . Previous experimental and theoretical studies demonstrated that Cu(100) is the most favorable crystal orientation for the C−C coupling process .…”
Section: Introductionmentioning
confidence: 99%